Pengukuran Kepuasan Nasabah Sekuritas (Studi Kasus: Galeri Investasi Di Kota Bandung) - Ragil Pardiyono; Jahny Sastradiharja (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research begins with a decrease in the number of securities companies from year to year which is inversely proportional to the increase in the SID of individual investors. The decrease in the number of securities companies was caused by some companies being unable to compete due to the minimal number of customers. One of the factors that determine the level of success of a company is the company's ability to provide quality service to customers to achieve satisfaction. So this study will measure customer satisfaction in securities companies using digital-based indicators (e-service). Data collection was carried out on securities company customers in several investment galleries at private universities in the city of Bandung. Data processing using the Customer Satisfaction Index (CSI) method, with the results of the processing concluded that the quality of securities companies perceived by customers is very satisfactory.